Regulating competition in the digital network industry / Jasper van den Boom. - Boom, Jasper van den (Global competition law and economics policy., 2026)
This book proposes a wholly new view on digital competition. Digital firms compete to capture parts of the digital network industry. Once they control access points for competition, they get to decide who gets to compete and how. With their superior access to information and users, incumbents become the de facto regulators of their part of the digital network. Regulation that focuses on markets cannot capture these dimensions of power and competition. The system of Progressive Ecosystem Regulation proposed in this book explains how ecosystem competition can be stimulated to create meaningful competitive pressures, open up the network, and introduce real choice for users.